Hepatoprotective activity of Sonchus asper in paracetamol-induced hepatic damage in rabbits - Ullah, Aftab-; Ahmad, Mahmood; Ahmad, Taseer; Naseer, Faiza Naseer (Bangladesh Journal of Pharmacology, 2015)
DOI: http://dx.doi.org/10.3329/bjp.v10i1.20620